Biopolymer-based nanocomposites as antimicrobial agents for water purification - Taka, Anny Leudjo; Monapathi, Mzimkhulu E.; Klink, Michael J. (Edelweiss Applied Science and Technology, 2025)
The increasing antimicrobial resistance (AMR) caused by commonly used antimicrobial agents during wastewater treatment processes has prompted the use of nanomaterials as alternative antimicrobial agents. The present study aimed to determine the antimicrobial activity of biopolymer nanocomposites synthesized using a combination of phosphorylation and cross-linking polymerization techniques. The synthesized biopolymer nanocomposite, pCh-MWCNTs@Ag-TiO2, along with its intermediate product (pCh-MWCNTs), was characterized using spectroscopy, thermogravimetric analysis, and microscopy techniques. Antimicrobial assays were conducted using agar well diffusion and MIC. FTIR analysis confirmed the presence of key functional groups in the synthesized polymers, including phosphate groups, carbamate linkages, and the Ti-O-C bond in the pCh-MWCNTs@Ag-TiO₂ polymer. TGA revealed three thermal degradation stages: moisture and solvent loss, carbamate decomposition, and breakdown of MWCNTs and chitosan. BET analysis indicated that the pCh-MWCNTs polymer exhibited the largest surface area, SEM micrographs displayed a porous, spongy structure, and EDS confirmed the presence of elements such as C, O, P, Ag, and Ti. XRD patterns showed an amorphous structure, suggesting that nanomaterial incorporation disrupts the semi-crystalline nature of chitosan. Biopolymers exhibited antimicrobial activity against tested microorganisms. The developed pCh-MWCNT@Ag-TiO2 biopolymers were more effective, especially against S. aureus. The increasing incidence of waterborne pathogens and associated AMR in wastewater environments warrants further research on biopolymer-based nanocomposites.